Investigation of Pulse Electric Field Influence on Cell Trypsinization Assay - Buhari Mamman, Hassan; Ishaku Abdul, Dalyop; Mahadi Abdul Jamil, Muhammad; Ahmed Bawa, Mohammed; Nazib Adon, Mohamad (International Journal of Engineering and Technology, 2018)
This study is aimed at investigating the effect of pulse electric field on cell attachment properties towards the enhancement of wound healing process. The Human Colorectal Adenocarcinoma cell line (HT29) was use in this study. The HT29 cells were treated with an electric field of 600V/cm amplitude for 500µs pulse duration in suspension and seeded for 24 hours. A time-lapse live imaging of the trypsinization assay of the HT29 cell was carried out using integrated devices for live cell imaging that was equipped with Charge Coupled Device (CCD) Camera, Temperature and Carbon IV Oxide (CO2)Controllers as well as, an Inverted Microscope. The electric treatment was found to decrease the adhesiveness of the cell by 41% where the treated cells detached from the substrate in 340 seconds as compared to control group that took 480 seconds to completely detached from the substrate immediately after trypsinization. Hence, the study suggested that the application of appropriate electric field, can affect the cell signalling pathways which in turn decrease the degree of cell adhesion on the substrate. The decrement in the cell adhesion could facilitate wound healing process via increased cellular migration, since the speed of cell migration is inversely proportional to the strength of cell adhesion.